Охота на крыс: повести / А. Кивинов - Кивинов Андрей (Русский проект, 1999)
Экземпляры: ф.1 (20180903) / Инвентарный номер: 55929 / Цена: 30.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 38 / ББК: 84(2Рос=Рус)6